2022
DOI: 10.3390/agronomy12051080
|View full text |Cite
|
Sign up to set email alerts
|

Species-Enriched Grass-Clover Mixtures Can Promote Bumblebee Abundance Compared with Intensively Managed Conventional Pastures

Abstract: (1) Land use intensification has led to serious declines in biodiversity, including in forage production systems for dairy cows. Agri-environmental schemes, such as enriching grasslands in floral species, were shown to be an effective tool to promote biodiversity in higher trophic levels. Here, we studied an innovative pasture-based dairy production system with floral-species-enhanced temporary grasslands, with respect to the effect on wild bee abundance and species richness. (2) We studied three grass–clover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Increasing summer floral availability in pastures would likely require delayed or alternated mowing (Pywell et al., 2011) in order to extend the flowering period. Alternatively, legumes such as Trifolium repens , T. pratense and Medicago sativa , which are among the top 10 species contributing to July flower cover in our study area (Table S8), can be sown in pastures to benefit bumblebees (Baude et al., 2016; Beye et al., 2022). These recommendations can be applied to other pasture‐dominated landscapes, but as our landscapes largely do not contain mass‐flowering crops, these crops likely need to be taken into account in management strategies in arable‐dominated landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing summer floral availability in pastures would likely require delayed or alternated mowing (Pywell et al., 2011) in order to extend the flowering period. Alternatively, legumes such as Trifolium repens , T. pratense and Medicago sativa , which are among the top 10 species contributing to July flower cover in our study area (Table S8), can be sown in pastures to benefit bumblebees (Baude et al., 2016; Beye et al., 2022). These recommendations can be applied to other pasture‐dominated landscapes, but as our landscapes largely do not contain mass‐flowering crops, these crops likely need to be taken into account in management strategies in arable‐dominated landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was carried out under management typical for silage production in the UK; however, further work looking at cultivars sown in a variety of seed mixtures is desirable. For example, inclusion of forbs in seed mixtures can support a greater diversity of pollinators (Beye et al, 2022; Brown et al, 2012; Woodcock et al, 2014), and identifying the best cultivars to include in diverse seed mixtures will be useful to farmers. Current initiatives aiming to reduce the negative impact of farming on the environment, such as the UK's Environmental Land Management Scheme (DEFRA, 2020) and the EU's European Green Deal (European Commission, 2019), are opportunities to better integrate pollinator‐friendly plant cultivars into farming.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was carried out under management typical for silage production in the UK; however, further work looking at cultivars sown in a variety of seed mixtures is desirable. For example, inclusion of forbs in seed mixtures can support a greater diversity of pollinators (Beye et al, 2022;Brown et al, 2012;Woodcock et al, 2014), and identifying the best cultivars to include in diverse seed mixtures will be useful to farmers. Current tors (Carvell et al, 2006;Goulson et al, 2005;Rundlöf et al, 2014;Timberlake et al, 2020), optimizing benefits for both groups should be a priority for future research.…”
Section: Vanessa Carduimentioning
confidence: 99%
“…Lavery et al, 2021)), or even eliminate it if designed to support a higher diversity of pollinators by including plants with different pollinator profiles in flower mixtures to enhance flower-visiting insects (Cong et al, 2020). In a comparison of grassland leys with increasing levels of diversity compared to a conventional monoculture of perennial ryegrass as permanent grassland, a study by Beye et al (2022) found that pollinator abundance increased drastically, with 541 wild bees of 10 species in the diverse grassland leys, compared to no wild bees in the permanent grassland due to the absence of flowers. Although pollinator abundance was not affected by the grassland ley diversity, the simple mixtures consisting of perennial ryegrass and white clover were only visited by common generalist species, whereas the multispecies grassland ley increased the abundance of rare long-tongued bumblebee to 10% in grazed areas, and even to 20% in ungrazed exclosures (Beye et al, 2022).…”
Section: Flower Resources For Pollinatorsmentioning
confidence: 99%